Integrating AI-Based Tools to Enhance Speaking Fluency in EFL Classrooms in Labuhanbatu Utara - Nguyen Hoang Anh; Afsaneh Baharloo; Gumarpi Rahis Pasaribu (JELIM : Journal of Education, Language, Social and Management, 2025)
This study explores the impact of integrating Artificial Intelligence (AI)-based tools on enhancing speaking fluency among English as a Foreign Language (EFL) students in Labuhanbatu Utara, Indonesia. Utilizing applications such as ELSA Speak and Google Speech-to-Text, the research implemented a classroom-based intervention involving 30 senior high school students over eight weeks. A mixed-method approach was employed, combining pre- and post-tests, classroom observations, and interviews with both students and teachers. The results revealed significant improvements in students’ fluency, pronunciation accuracy, and speaking confidence. Additionally, the AI tools fostered greater learner autonomy, increased motivation, and encouraged active classroom participation. Despite certain challenges related to infrastructure and digital accessibility, the overall findings suggest that AI technologies can effectively support and enrich speaking instruction in EFL settings, particularly in rural or under-resourced contexts. The study offers practical insights for educators aiming to enhance oral proficiency through technology-enhanced language learning.